Development of a unified model to predict the axial stress–strain behavior of recycled aggregate concrete confined through spiral reinforcement. (1st September 2020) - Munir, Muhammad Junaid; Kazmi, Syed Minhaj Saleem; Wu, Yu-Fei; Patnaikuni, Indubhushan; Wang, Junfeng; Wang, Quan
Highlights: The stress–strain behavior of steel spiral confined NAC, RAC and TRAC is studied. General stress–strain model of steel spiral confined NAC, RAC and TRAC is developed. A relationship is provided to calculate the permissible content of any source of RCA. Abstract: Utilizing the confinement from transverse reinforcement of compression members to offset the inferior recycled aggregate concrete (RAC) performance is considered a sustainable and adaptable way to solve the problems related to the application of recycled coarse aggregates (RCA). Prediction of the axial stress–strain behavior of RAC is a challenging task due to variation in the physical properties of RCA from different sources. Currently, limited work is available in the literature to predict the axial stress–strain behavior of steel spiral confined RAC applicable to RCA from different sources. In this study, a general axial stress–strain model of steel spiral confined normal aggregate concrete (NAC), RAC and treated recycled aggregate concrete (TRAC) is developed considering the material characteristics of RCA. For this purpose, the axial stress–strain behavior of steel spiral confined NAC, RAC, and TRAC having different target strengths and confinement levels is studied. The results of this study show that confinement has a more prominent effect on peak and ultimate strains of RAC and TRAC than NAC. The axial stress–strain model developed in this study, considering a large test database, can be used to predict the performance of steel spiral confined NAC, RAC, and TRAC for any source/type of RCA leading towards the development of design guidelines for sustainable RAC members. Moreover, a relationship is also provided to calculate the permissible content of RCA having any type/source to achieve the compressive strength of steel spiral confined RAC or TRAC similar to NAC for any confinement pressure and concrete strength.